Mobile Internet: Enabling Technologies and Services - K Salkintzis, Apostolis (CRC Press, 2009)
Consumers want it, businesses are demanding it. The migration of Internet services to a mobile environment is inevitable. But while the ability to be on the go and connected to the Internet sets the stage for increased efficiency and productivity, many technical challenges associated with user mobility and wireless connectivity remain.